2019
DOI: 10.1016/j.heliyon.2019.e02112
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the mechanical properties of zirconia/Nafion® nanocomposite membrane through carbon nanotubes for fuel cell application

Abstract: Membranes are widely used daily, such as for filtration in reverse osmosis, or in the form of electrolyte membrane fuel cells. Modified Nafion ® membranes were synthesised by impregnation and their mechanical properties were observed. The effect of the incorporation of a ZrO 2 -CNT nano-filler within Nafion ® membrane on the thermal stability and crystallinity was investigated by TGA and XRD. Tensile test results show the increases in the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Type I is conventional PNCs, which are PNCs created from polymeric nanocomposites to increase their characteristics but without adding a function to the membrane. The membrane is enhanced in this scenario, but it remains a passive element in separation systems, with the primary and unique role of separating components of the feed phase through two different mechanisms, ion exchange and ionic exchange, in addition to size exclusion or dissolution–diffusion [ 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. Type II is the active-bulk phase PNCs, which are PNCs made from polymeric nanocomposites that give the membrane the ability to perform dual functions, one major function linked to mass transfer between two separated phases and a second function linked to specific properties of the material from which it is made; an example of this is a PNC made from inorganic nanoparticles distributed in a polymeric phase based on a conductive polymer such as poly(aniline) [ 108 , 109 , 110 , 111 , 112 ].…”
Section: Membranes Made Of Polymeric Nanocomposite (Pnc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Type I is conventional PNCs, which are PNCs created from polymeric nanocomposites to increase their characteristics but without adding a function to the membrane. The membrane is enhanced in this scenario, but it remains a passive element in separation systems, with the primary and unique role of separating components of the feed phase through two different mechanisms, ion exchange and ionic exchange, in addition to size exclusion or dissolution–diffusion [ 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. Type II is the active-bulk phase PNCs, which are PNCs made from polymeric nanocomposites that give the membrane the ability to perform dual functions, one major function linked to mass transfer between two separated phases and a second function linked to specific properties of the material from which it is made; an example of this is a PNC made from inorganic nanoparticles distributed in a polymeric phase based on a conductive polymer such as poly(aniline) [ 108 , 109 , 110 , 111 , 112 ].…”
Section: Membranes Made Of Polymeric Nanocomposite (Pnc)mentioning
confidence: 99%
“…In the case of porous membranes, more specifically RO membranes, the solvent will penetrate the structure of the membrane, which will lead to two outcomes: the polymer phase has a high affinity with the membrane, and as a result, it is possible that strong solvation interactions will occur, which will promote the decrease in the permeability, which will result in a decrease of the effective pore radius; however, it is also very likely that the membrane will exhibit poor mechanical performance under these conditions. In circumstances such as these, the nanocomponent of the PNC contributes to the attenuation of the effect [ 101 , 102 , 103 , 104 , 105 , 106 ]. Because there is no affinity between the solvent and the membrane, solvation does not take place, the membrane material’s mechanical properties remain unchanged, and solute dissolution in the membrane phase can be easily understood by using the solute–membrane affinity in terms of relative size in relation to the membrane cut-off.…”
Section: Mechanism Of Separation Of Pncmentioning
confidence: 99%
“…[86][87][88] CNT are inorganic additives with improved mechanical and thermal properties as well as low electrical diffusion thresholds. 89 Individual nanotube mechanical properties are more easily transferred to the macro scale compared to electrical and thermal characteristics. Figure 5 compares the best CNT fibres with conductive metals in terms of normal strength and stiffness.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Carbon nanotubes (CNT) have excellent mechanical qualities, are inexpensive, and also have excellent electrical conductivity 86‐88 . CNT are inorganic additives with improved mechanical and thermal properties as well as low electrical diffusion thresholds 89 . Individual nanotube mechanical properties are more easily transferred to the macro scale compared to electrical and thermal characteristics.…”
Section: Versatile Properties Of G‐c3n4 Cnt and Graphene‐based Membra...mentioning
confidence: 99%
“…In addition, diminishing of fuel crossover and enhancing of the mechanical and thermal strength has been adequately satisfied by modification of these nanomaterials . For instance, Sigwadi et al impregnated a ZrO 2 ‐CNT nanoparticle into a Nafion polymer matrix and found that the mechanical properties and water retention of the nanocomposite membrane was enhanced compared with the plain Nafion 117. Besides, the hygroscopic nature of titanium oxide made it as a potential candidate to be used in PEM since it retains the water under fuel cell operations and also improves the mechanical attributes .…”
Section: Introductionmentioning
confidence: 99%